Low threshold and efficient multiple exciton generation in halide perovskite nanocrystals - Li, Mingjie (Nat Commun, 2018)
Multiple exciton generation (MEG) or carrier multiplication, a process that spawns two or more electron–hole pairs from an absorbed high-energy photon (larger than two times bandgap energy E(g)), is a promising way to augment the photocurrent and overcome the Shockley–Queisser limit. Conventional semiconductor nanocrystals, the forerunners, face severe challenges from fast hot-carrier cooling. Perovskite nanocrystals possess an intrinsic phonon bottleneck that prolongs slow hot-carrier cooling, transcending these limitations. Herein, we demonstrate enhanced MEG with 2.25E(g) threshold and 75% slope efficiency in intermediate-confined colloidal formamidinium lead iodide nanocrystals, surpassing those in strongly confined lead sulfide or lead selenide incumbents. Efficient MEG occurs via inverse Auger process within 90 fs, afforded by the slow cooling of energetic hot carriers. These nanocrystals circumvent the conundrum over enhanced Coulombic coupling and reduced density of states in strongly confined nanocrystals. These insights may lead to the realization of next generation of solar cells and efficient optoelectronic devices.